Creation of an Industrial Bacillus thuringiensis Strain With High Melanin Production and UV Tolerance by Gene Editing - Zhu, Lingyi; Chu, Yawen; Zhang, Bowen; Yuan, Ximu; Wang, Kai; Liu, Zhiyu; Sun, Ming (Frontiers in Microbiology, 2022)
Bacillus thuringiensis produces insecticidal crystal proteins (ICPs) which exhibit strong insecticidal toxicity. But when used in the field, ICPs would be destroyed by ultraviolet (UV) radiation in sunlight, thus decreasing the insecticidal activity and shortening the persistency. To improve the duration of B. thuringiensis preparations, we endowed a highly toxic industrial B. thuringiensis HD-1 with UV tolerance by making it produce melanin, a pigment that absorbs UV radiation. In B. thuringiensis, melanin is derived from homogentisate (HGA), an intermediate in the tyrosine pathway. And the absence of homogentisate-1,2-dioxygenase (HmgA) will lead to the formation of melanin. In this study, we used the CRISPR/Cas9 system to knock out the hmgA gene and obtained a melanin-producing mutant HD-1-△hmgA from strain HD-1. The melanin yield by mutant HD-1-△hmgA reached 3.60 mg/mL. And the anti-UV test showed that melanin serves as a protection to both the organism and the ICPs. After UV irradiation for 3 h, mutant HD-1-△hmgA still had an 80% insecticidal activity against the cotton bollworm, Helicoverpa armigera, while the control line only had about 20%. This study creates a light-stable biopesticide prototype based on a classic industrial strain that can be applied directly and takes the melanin-producing strain as a concept to improve the preparation validity.